Curved-folding origami design - Mitani, Jun, 1975- (Boca Raton, Florida : CRC Press, 2019)
The origami introduced in this book is based on simple techniques. Some were previously known by origami artists and some were discovered by the author. Curved-Folding Origami Design shows a way to explore new area of origami composed of curved folds. Each technique is introduced in a step-by-step fashion, followed by some beautiful artwork examples. A commentary explaining the theory behind the technique is placed at the end of each chapter. Features Explains the techniques for designing curved-folding origami in seven chapters Contains many illustrations and photos (over 140 figures), with simple instructions Contains photos of 24 beautiful origami artworks, as well as their crease patterns Some basic theories behind the techniques are introduced
Prologue -- Fold a curve -- Aligning curves -- Aligning rotated curves -- Tucking -- Folding cones -- Folding back at straight line -- Other techniques -- Afterword.
OCLC-licensed vendor bibliographic record.
Keywords: Origami; Folds (Form); Paper work; CRAFTS & HOBBIES / Carving; MATHEMATICS / General; MATHEMATICS / Geometry / General; MATHEMATICS / Recreations & Games